Perceived exercise limitation in asthma: The role of disease severity, overweight, and physical activity in children1. Issue 1 (11th November 2016) - Westergren, Thomas; Berntsen, Sveinung; Lødrup Carlsen, Karin C.; Mowinckel, Petter; Håland, Geir; Fegran, Liv; Carlsen, Kai‐Håkon
Abstract: Background: Children with asthma may be less physically active than their healthy peers. We aimed to investigate whether perceived exercise limitation (EL) was associated with lung function or bronchial hyper‐responsiveness (BHR), socioeconomic factors, prenatal smoking, overweight, allergic disease, asthma severity, or physical activity (PA). Methods: The 302 children with asthma from the 10‐year examination of the Environment and Childhood Asthma birth cohort study underwent a clinical examination including perceived EL (structured interview of child and parent(s)), measure of overweight (body mass index by sex and age passing through 25 kg/m 2 or above at 18 years), exercise‐induced bronchoconstriction (forced expiratory volume in one‐second (FEV1 ) pre‐ and post‐exercise), methacholine bronchial challenge (severe BHR; provocative dose causing ≥20% decrease in FEV1 ≤ 1 μmol), and asthma severity score (dose of controller medication and exacerbations last 12 months). Multivariate logistic regression analyses were conducted to assess associations with perceived EL. Results: In the final model explaining 30.1%, asthma severity score (OR: 1.49, (1.32, 1.67)) and overweight (OR: 2.35 (1.14, 4.82)) only were significantly associated with perceived EL. Excluding asthma severity and allergic disease, severe BHR (OR: 2.82 (1.38, 5.76)) or maximal reduction in FEV1 post‐exercise (OR: 1.48 (1.10, 1.98)) and overweight (OR: 2.15 (1.13, 4.08) and 2.53 (1.27, 5.03)) explained 9.7% and 8.4% of perceived EL, respectively. Conclusions: Perceived EL in children with asthma was independently associated with asthma severity and overweight, the latter doubling the probability of perceived EL irrespectively of asthma severity, allergy status, socioeconomic factors, prenatal smoking, or PA. Abstract :